Isolation and identification of Actinomycetes with antifungal activity from karts ecosystem in Maros-Pangkep, Indonesia - HERLINA RANTE; MARIANTI A. MANGGAU; GEMINI ALAM; ERMINA PAKKI; ANDI EVI ERVIANI; NUR HAFIDAH; HAMDAYANI LANCE ABIDIN; ALIMUDDIN ALI (Society for Indonesian Biodiversity, 2024)
Abstract. Rante H, Manggau MA, Alam G, Pakki E, Erviani AE, Hafidah N, Abidin HL, Ali A. 2024. Isolation and identification of Actinomycetes with antifungal activity from karts ecosystem in Maros-Pangkep, Indonesia. Biodiversitas 25: 458-464. Actinomycetes have yielded various biologically active secondary compounds with intriguing properties like antimicrobial, antiviral, and anticancer effects. This research aimed to isolate, identify, and screen the antifungi from soil environmental samples collected from the karst ecosystem in Maros-Pangkep, Indonesia. The active isolate is then fermented for the production of secondary metabolites. The fermentation process uses an M1 medium under agitated conditions at 150 rpm for 12 days. The isolate Actinomycetes were identified based on sequence gen 16S rRNA. Screening of antifungal activity was carried out against Candida albicans ATCC 10231 and Aspergillus niger ATCC 16404 by antagonistic test. The diffusion method was applied using the paper disc to assess the antifungal activity. The result revealed that 8 isolates were purified from the soil samples collected. From the 8 isolates of Actinomycetes obtained, two Actinomycetes exhibited antifungal activities in the screening methods, namely isolates with code B11 and B 17. The crude extract of isolate B11 was active against C. albicans and A. niger at concentrations of 2 mg/paper disc, 1.5 mg/paper disc, and 0.75 mg/paper disc. Furthermore, isolate B17 was found to be only active against C. albicans. The phylogenetic analysis of the 16S rRNA gene sequences indicated that B11 showed the highest similarity to Streptomyces tuirus strain NBRC 15617.